QUANTIFY CHANGES IN AGRICULTURE LAND USING SUPERVIESD CLASSIFICATION METHOD FOR REWARI DISTRICT, HARYANA (International Journal of Food and Nutritional Sciences, 2023)
Land is a paramount natural resource. The city's population increases, accompanied by changes in geographic dimensions. Nevertheless, it is impossible to impede the natural process of land transformation. This study examines the evolution of highways. A change detection model was executed in ERDAS. Envision assessing land usage and land cover, particularly agricultural land, from 2006 to 2021. Five forms of land use were identified, with built-up agricultural land as the most prevalent type. A notable transformation has been recorded during 16 years (2006-2021) in Deodhai hamlet, situated 10 km from Rewari, Haryana, enabled by ERDAS, subsequent to the completion of the NH-48 highway. In 2006, 61.78% of the land was allocated for agricultural use, declining to 48.67% by 2021. The principal reason driving this alteration in land use is road construction.